Grenada : Staff Report for the 2001 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Grenada's economic performance in recent years has been positive owing to the government's strategy of focusing on promoting private investment. The IMF staff commends the government for its commitment to maintaining fiscal prudence, and pursuing reforms aimed at creating an environment that is conducive for foreign investment. Addressing the revenue weakness by initiating a review of exemptions is required. One of the weaker aspects of fiscal policy in Grenada is debt management. Available indicators appear to point to a broadly sound domestic banking system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet